The motion of a curling rock - Penner, A. R. (Vancouver Island University, 2014)
A model based on a scratch-guide mechanism being responsible for the curl of a curling rock is presented. The model is based on the postulate that when the asperities around the rear of the running band of a curling rock cross the scratches produced by the front of the running band, at an angle due to the rotation of the curling rock, a sideways force will be exerted on them. It is shown that such a mechanism does lead to a curl distance of the correct magnitude and one that is insensitive to angular velocity. The model is then compared to previous experimental results where it is found to be in good agreement.